ELASTIC AND PLASTIC DEFORMATION OF STRENGTHENED FERRO-CONCRETE CONSTRUCTIONS - M N Serazutdinov; M N Ubaydulloyev (Structural Mechanics of Engineering Constructions and Buildings, 2013)
The article presents the variational method for stress-strain state evaluation of ferro-concrete beam structures strengthening under load. The presented method allows us to con sider the changes of cross sectional sizes, existence of repair stresses, tension imposing, resulting from the reinforcement of a structure. The calculation results illustrating features of tension of the strengthened ferro-concrete construction were given.